De verso em verso se aprende história: uma “História do Crato” a partir da do intelectual Elói Teles de Morais - Landim, Ossian Soares (2022)
What is an intellectual? What are the characteristics of an intellectual? What are the actions of an intellectual? Where does the intellectual circulate? How can you prove that a person is intellectual? Cordel literature has been present in the lives of Northeasterners since the end of the 19th century. Cordel is a pamphlet composed of rhyming poems, with different themes such as: religion, politics, romance, social, environmental, etc. The term cordel comes from the Iberian Peninsula and was later used here in Brazil to designate popular northeastern literature. In some cases, popular poets compose strings with themes about historical events, for that, they use certain sources such as: speeches, newspapers, chronicles, etc. Some of these speeches are produced by intellectuals who were members of renowned entities. Through this information, cordel literature, as well as its authors, are sources of analysis of the human and social sciences. For a long time, cordel literature and poets were left out of the canon of Brazilian literature because they were considered second-class texts and authors. of lower class. The aim of this thesis is to compare the discourses of intellectuals, chroniclers of the 20th century and more recent researchers of the 21st century on the history of Crato with the narratives of three cordelists written between 1992 and 1993 by the cordelist and member of the Academia dos Cordelistas do Crato ( ACC) Mr. Elói Teles de Morais (Senhor Elói or Elóia), in order to perceive the similarities and differences in the speeches and poetry of cordel and affirm that the cordelist is an intellectual due to his actions before society such as: social and political claims, in addition to articulating together with other intellectuals in the same area for the conquest of physical and subjective spaces. In order for this research to be successful, we analyzed printed sources available on the websites of the entities to which intellectuals and researchers published their speeches: Instituto Cultural do Cariri (ICC), Instituto do Ceará (IC), Instituto Histórico e Geográfico Brasileiro (Brazilian Historical and Geographical Institute) IHGB), Ceará Academy of Letters (ACL), Federal University of Ceará (UFC). The theoretical contribution of the research revolved around an interdisciplinarity between cultural history, sociology, and the history of popular literature. In view of the analyzed sources, the result was that intellectuality is not in the eloquence of speeches or only added to belonging to an institution. This research found that in the field of popular literature, the cordelista is an intellectual with skills and ideologies within his field of activity.